Características de las alternativas energéticas de combustibles sólidos de tres especies del bosque varillal de Nina Rumi, Loreto-Perú, 2020 - Pérez Vera, Christian Orlando (2022)
In the present study, the characteristics of the energetic alternatives of solid fuels of Inga tarapotensis Spruce ex Benth were determined. “varillal shimbillo”, Miconia poeppigii Triana. "rifari" and Hevea guianensis Aubl. “shiringa” from the varillal forest of Nina rumi. To obtain the samples, a selection of the inventory of the varillal forests was carried out, wood samples were extracted taking into account the basic densities of the wood, then transported to the laboratory of Chemistry and Wood Energy of the Faculty of Forestry Sciences for the tests using an electric muffle up to 1200 °C temperature. The data obtained were calculated using validated formulas. The results show that the highest yields in toasted wood and charcoal have been determined in Inga tarapotensis Spruce ex Benth. “varillal shimbillo”, Miconia poeppigii Triana. "rifari" with 73.68% and 72.83%; 41.35% and 39.50%, respectively. The highest calorific value was determined in "shimbillo de varillal" coal with 8243.25 Kcal/Kg, followed by "rifari" with 8186.29 Kcal/Kg. Comparing the difference in means with the Tukey and Bonferroni test, it has been determined that they are not significant. There is a high positive correlation between the basic density of the wood with the apparent density, yield of toasted wood, charcoal, and the calorific value of the charcoal in the evaluated species. Carry out energy plantations with species that have a higher yield of toasted wood and charcoal, as well as having a higher calorific value.